Business Model Analysis at Tempeh Macaca Chips MSME With SWOT Analysis on Business Model Canvas Approach - Restuwidjaja, Marisa; Retnaningsih (Business Review and Case Studies, 2025)
Background: The Macaca Tempe Chips SME is a business in South Tangerang City that has successfully processed raw tempeh into tempeh chips that are worth selling but need more human resources, which has implications for declining sales.Purpose: This study aims to obtain alternative business development strategies by identifying the Business Model Canvas owned by Macaca Tempe Chip MSMEs.Design/methodology/approach: The method used was qualitative, with the Business Model Canvas approach and SWOT analysis. Elements of BMC were analyzed descriptively, and then a SWOT analysis was carried out for each aspect. The respondents in this study consisted of internal respondents, namely the owner of the Macaca Tempe Chips (MSME), and external respondents consisting of experts, consumers, and potential consumers of Macaca Tempe Chips.Findings/Result: The SWOT analysis resulted in six strategies applied to the elements of the canvas business model (BMC1). The final stage of analysis shows that the results of validating the business model canvas (BMC2) need additional strategies in the channel and critical partner elements. Conclusion: According to the research findings, several alternatives should be implemented in the business processes of Macaca Tempe Chips MSMEs. These include optimizing marketing channels, expanding partnerships, recruiting skilled human resources, providing human resource training, purchasing production equipment, and enhancing product innovation and quality.Originality/value (State of the art): The absence of business analysis conducted on Macaca Tempe Chips MSME is a novelty of this research.Keywords: alternative strategy, business model canvas, human resources, MSME, SWOT analysis